Liberalisation, urban governance and gridlock: Diagnosing Yangon's mobility crisis. (January 2019) - Fox, Sean; Ney, David; Verrucci, Enrica
Abstract: The city of Yangon is home to over 5 million people, hosts Myanmar's largest port and produces a disproportionate share of national output. But a mobility crisis is undermining the city's economic potential and contributing to a deteriorating quality of life for its residents. The most obvious symptom of this crisis is acute traffic congestion. The proximate causes are clear: growing demand for journeys, a surge in vehicle numbers, a modal shift away from buses, and myriad 'flow disruptions'. However, solving this mobility crisis requires recognizing the underlying causes, including a 'congestion incentive spiral' fuelled by rapid liberalisation of vehicle imports in a context where there are few viable alternatives to buses and private automobiles. This situation is a direct consequence of systematic failures in urban planning, investment and regulation linked to active neglect from successive military regimes and dysfunctional institutional arrangements. To preserve its rich urban heritage, Yangon will need to embrace 21st century integrated planning practices that seek to maximise accessibility and mobility for all people rather than minimise traffic congestion for those who use cars. Highlights: Yangon's economy is growing rapidly in the current context of liberalisation Rapid growth coupled with a legacy of underinvestment and laissez-faire transport governance has resulted in acute traffic congestion A 'congestion incentive spiral' has set in, accelerating a modal shift from widespread use of buses to increasing use of private auto transport Acute congestion is simply the most visible symptom of a broader mobility crisis In the short run, reviving BRT plans and encouraging cycling would improve mobility In the long run a substantial restructuring of urban governance is required to keep the city moving